Who Sets the Agenda? - Oji, Majority (Direct Research Journal of Social Science and Educational Studies, 2024)
The research focused on agenda-setting procedures and their practical implications, taking a qualitative approach to emphasize the significance of agenda-setting processes in shaping public discourse. The study examined agenda setting in relation to reality, media, and public perception, and carefully considered the arguments to determine the most effective methods for setting and promoting an agenda. The conclusion highlighted the critical role of agenda-setting in shaping public discourse, policy priorities, and resource allocation. It emphasized the importance of understanding how various actors and factors influence the agenda in order to navigate and influence the political and social landscape effectively.